Kontribusi Pendidikan Biologi Terhadap Pencapaian Delapan Tujuan SDGs: Systematic Literature Review - Ranti Fauziah; Aryani Dwi Kesumawardani; Eko Kuswanto; Raicha Oktafiani (WISE Pendidikan Indonesia, 2026)
Sustainable Development Goals (SDGs) emphasize the importance of education in supporting sustainable development, including through biology education. However, studies discussing the contribution of biology education to SDGs remain fragmented and generally focus on specific aspects. Therefore, this study aimed to identify publication trends, map the contribution of biology education toward SDG 4, SDG 6, SDG 7, SDG 11, SDG 12, SDG 13, SDG 14, and SDG 15, and formulate directions for sustainability-oriented biology learning development based on literature synthesis. This study employed a descriptive qualitative approach using the Systematic Literature Review (SLR) method with PRISMA stages, including identification, screening, eligibility, and inclusion. Articles were collected through Google Scholar using the Publish or Perish application. From 1,121 identified articles, 30 articles published between 2021–2025 in SINTA and Scopus-indexed journals were selected based on inclusion and exclusion criteria. The results indicated that biology education contributed significantly to SDG 4, SDG 13, and SDG 15 through innovative learning models, Education for Sustainable Development (ESD), scientific literacy, climate change education, biodiversity conservation, and ecology-based learning. Meanwhile, contributions to SDG 7, SDG 12, and SDG 14 were still limited. These findings indicate that biology education plays a strategic role in developing sustainability competencies by integrating scientific understanding, environmental awareness, and sustainability-related skills within the learning process. The findings may serve as a basis for developing ESD-oriented biology curricula and strengthening future research on underrepresented SDGs, particularly sustainable energy, responsible consumption and production, and marine ecosystem conservation. Nevertheless, the findings should be interpreted within the methodological scope of this review, which relied on Google Scholar as the primary database and did not include a formal quality appraisal process.